Dog ownership satisfaction determinants in the owner-dog relationship and the dog's behaviour - Herwijnen, Ineke R. van; van der Borg, Joanne A. M.; Naguib, Marc; Beerda, Bonne (PLOS ONE, 2018)
Dog ownership satisfaction relates to the quality of life of both owner and dog, and when seriously compromised may even lead to dog abandonment. Knowledge on determinants of dog ownership satisfaction is limited, obstructing solutions for promoting satisfaction, and here we quantified causes making dog owners less than very satisfied with their dog. We focused on the owner perceived relationship with the dog, unwanted dog behaviour, and dog obedience class attendance. The study population included only few seriously dissatisfied dog owners, preventing discrimination of multiple levels below ‘very satisfied’. Consequently, existing relationships in the entire population may have been missed or underestimated and the findings apply specifically to dog owners that are relatively contented with dog ownership. Nine hundred seventy-seven Dutch dog owners completed an online questionnaire and we found the probability of being very satisfied to associate with all three subscales of the Monash Dog Owner Relationship Scale. Most strongly with perceived costs of ownership and less so with shared activities between owner and dog, and perceived emotional closeness to the dog. Aggression and/or disobedience related directly to high perceived ownership costs and to an increased probability of being less than very satisfied. Interaction effects indicated that dog disobedience was less influential on ownership satisfaction at high levels of aggression. Surprisingly, dog ownership satisfaction was unrelated to dog obedience class attendance, raising questions about the effectiveness of these classes in establishing satisfying dog-owner relationships. Training aids used during classes could play a role here, as choke chain use associated with high perceived costs and increased probabilities of being less then very satisfied with dog ownership. Ownership satisfaction in relatively contented dog owners, seems more influenced by unwanted dog behaviour and perceived costs of ownership, than by perceived emotional closeness to the dog, shared activities and dog obedience class attendance.